Gulags, crime, and elite violence: Origins and consequences of the Russian mafia - Jakub Lonsky (Bank of Finland, Institute for Economies in Transition (BOFIT), 2020)
This paper studies the origins and consequences of the Russian mafia (vory-v-zakone). I web scraped a unique dataset that contains detailed biographies of more than 5,000 mafia leaders operating in 15 countries of the (former) Soviet Union at some point between 1916 and 2017. Using this data, I first show that the Russian mafia originated in the Gulag - the Soviet system of forced labor camps which housed around 18 million prisoners in the 1920s1950s period. Second, I document that the distance to the nearest camp is a strong negative predictor of mafia presence in Russia's communities in the early post-Soviet period. Finally, using an instrumental variable approach which exploits the spatial distribution of the gulags, I examine the effects of mafia presence on local crime and elite violence in mid-1990s Russia. In particular, I show that the communities with mafia presence experienced a dramatic rise in crime driven by turf wars which erupted among rival clans around 1993 and persisted for much of the 1990s. Further heterogeneity analysis reveals that mafia presence led to a spike in attacks against businessmen, fellow criminals, as well as law enforcement officers and judges, while politically-motivated violence remained unaffected.
URN:NBN:fi:bof-202011032479
Keywords: K42; N40; P16; P37; 330; Russian mafia; Gulag; Post-socialist transition; Crime; Elite violence